Lung Cancer Survival and Functional Polymorphisms in MBL2, an Innate-Immunity Gene - Pine, Sharon R. (J Natl Cancer Inst, 2007)
BACKGROUND: The relationship among chronic inflammation, innate immunity, and cancer is well established. Mannose-binding lectin (MBL) is a key player in innate immunity. Five polymorphisms in the promoter and first exon of the MBL2 gene alter the expression and function of MBL in humans and are associated with inflammation-related disease susceptibility. These five polymorphisms create six well-characterized haplotypes that result in lower (i.e., LYB, LYC, HYD, and LXA) or higher (i.e., HYA and LYA) serum MBL concentrations. We investigated whether survival of patients with lung cancer was associated with these polymorphisms. METHODS: We used a multivariable Cox proportional hazards model to study the association between MBL2 polymorphisms and their haplotypes and diplotypes in 558 white and 173 African American patients with non–small-cell lung cancer in the Baltimore, MD, area and lung cancer mortality. Smoking history and race were obtained from interviews, tumor stage was obtained from medical records, and cause of death was obtained from the National Death Index. All statistical tests were two-sided. RESULTS: We found a statistically significant association between the X allele of the promoter Y/X polymorphism (which results in a lower serum MBL concentration) and improved lung cancer survival among white patients (risk ratio [RR] of death from lung cancer with X/X or X/Y genotype compared with Y/Y genotype = 0.61, 95% confidence interval [CI] = 0.46 to 0.81) but not among African American patients (RR = 1.11, 95% CI = 0.69 to 1.77). The associations among white patients were strongest in heavy smokers and were independent of stage. We also found a statistically significant interaction between the Y/X polymorphism and race for lung cancer survival (P(interaction) = .019). The MBL2 LXA haplotype and XA/B diplotype, which are also associated with low serum MBL levels, were statistically significantly associated with improved lung cancer survival among white patients. CONCLUSION: The functional Y/X polymorphism of the innate-immunity gene MBL2 and MBL2 haplotypes and diplotypes appear to be associated with lung cancer survival among white patients.